Women's Reproductive Coercion and Pregnancy Avoidance: Associations With Homicide Risk, Sexual Violence, and Religious Abuse. (October 2021) - Bagwell-Gray, Meredith E.; Thaller, Jonel; Messing, Jill T.; Durfee, Alesha
This survey study explores patterns of reproductive coercion (RC) and pregnancy avoidance (PA) among women recruited from domestic violence shelters in the southwestern United States ( N = 661). Two logistic regression models assessed the demographic, relationships, and violence characteristics associated with RC and PA. Younger, African American, and Hispanic women were more likely to experience RC. Homicide risk, sexual intimate partner violence (IPV), and religious abuse were associated with RC, and RC and homicide risk were associated with PA. We discuss implications of the associations between RC and PA and their links to religious abuse, sexual IPV, and homicide risk.